Crystal engineering principles: fluoroquinolone salts - Dandela, Rambabu; Nangia, Ashwini (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: ciprofloxacin; Fluoroquinolone; norfloxacin

Crystal engineering of a zwitterionic drug to neutral cocrystals: a general solution for floxacins - Gunnam, Anilkumar; Suresh, Kuthuru; Ganduri, Ramesh; Nangia, Ashwini (Chemical Communications, 2016)
The transformation of zwitterionic Sparfloxacin (SPX) to the neutral form is achieved by cocrystallization. Neutral forms of drugs are important for higher membrane permeability, while zwitterions are more soluble in water. The twin advantages of higher solubility/dissolution rate and good stability of neutral SPX are achieved in a molecular cocrystal compared to its zwitterionic SPX hydrate. The amine-phenol supra-molecular synthon drives cocrystal formation, with the paraben ester acting as a "proton migrator'' for the ionic to neutral transformation.

Curcumin: pharmaceutical solids as a platform to improve solubility and bioavailability - Suresh, Kuthuru; Nangia, Ashwini (Crystengcomm, 2018)
Curcumin (CUR) is the prime curcuminoid in the Indian dietary spice turmeric, Curcuma longa, a plant of the Zingiberaceae family. CUR has promising and diverse therapeutic benefits, such as antioxidant, anti-inflammatory, antitumor, anti-hyperglycemic, antimalarial, antibacterial, and antiviral activity, including anti-Alzheimer's disease. However, CUR is yet to reach the status of a therapeutic drug candidate mainly because a standard solid dosage of curcumin suffers from poor oral bioavailability (0.05 g mL(-1), less than 1%). The reasons behind its low bioavailability include poor solubility (<8 g mL(-1) in water), low permeability and absorption, and rapid metabolism (short elimination half-life of <2 h). A successful CUR therapy requires an appropriate formulation system that will enhance the bioavailability and offer greater therapeutic efficacy. This review covers a comprehensive description of the CUR pharmaceutical solids, such as polymorphs, cocrystals, eutectics, and coamorphous solid-state forms with aim to determine ways to improve its physicochemical properties, including dissolution rate, solubility, physicochemical stability, mechanical strength, compressibility for tablet formation, and oral bioavailability. The cumulative publications in the past decade have forecast a bright future for development of an oral drug formulation of curcumin.

Curcumin-artemisinin coamorphous solid: Xenograft model preclinical study - Mannava, M. K. Chaitanya; Suresh, Kuthuru; Bommaka, Manish Kumar; Konga, Durga Bhavani; Nangia, Ashwini (Pharmaceutics, 2018)
Curcumin is a natural compound present in Indian spice turmeric. It has diverse pharmacological action but low oral solubility and bioavailability continue to limit its use as a drug. With the aim of improving the bioavailability of Curcumin (CUR), we evaluated Curcumin-Pyrogallol (CUR-PYR) cocrystal and Curcumin-Artemisinin (CUR-ART) coamorphous solid. Both of these solid forms exhibited superior dissolution and pharmacokinetic behavior compared to pure CUR, which is practically insoluble in water. CUR-ART coamorphous solid showed two fold higher bioavailability than CUR-PYR cocrystal (at 200 mg/kg oral dose). Moreover, in simulated gastric and intestinal fluids (SGF and SIF), CUR-ART is stable up to 3 and 12 h, respectively. In addition, CUR-PYR and CUR-ART showed no adverse effects in toxicology studies (10 times higher dose at 2000 mg/kg). CUR-ART showed higher therapeutic effect and inhibited approximately 62% of tumor growth at 100 mg/kg oral dosage of CUR in xenograft models, which is equal to the positive control drug, doxorubicin (2 mg/kg) by i.v. administration.

Cocrystals, salts, and supramolecular gels of nonsteroidal anti inflammatory drug niflumic acid - Mittapalli, Sudhir; Mannava, M. K. Chaitanya; Sahoo, Rasmita; Nangia, Ashwini (Crystal Growth & Design, 2019)
Niflumic acid (NFA) is a nonsteroidal anti-inflammatory drug (NSAID) classified under the BCS (Biopharmaceutical Classification System) Class II category of poor aqueous solubility and high permeability. In an attempt to improve the physicochemical properties of NFA, particularly solubility and dissolution rate by cocrystallization and salt formation, cocrystals of NFA were prepared with caprolactam (CPR, 1:1) and 2-hydroxy pyridine (2HP, 1:1) as well as salts with piperazine (PIP, 1:0.5), benzenesulfonic acid (BSA, 1:1), benzyl amine (BZA, 1:1 and 2:2), and tyramine (TYA, 1:1). The new solid forms were characterized by powder X-ray diffraction, infrared spectroscopy, and differential scanning calorimetry and confirmed by single crystal X-ray diffraction. In the cocrystals NFA CPR and NFA-2HP, the cyclic amide of the coformer forms a dimer synthon through N-H center dot center dot center dot O hydrogen bonds and such dimers extend through O-H center dot center dot center dot O hydrogen bonds. In piperazine, benzyl amine, and tyramine salts, proton transfer occurs from the NFA to the basic nitrogen of the coformer, and in NFA BSA salt, the proton is transferred from benzenesulfonic acid to the pyridine nitrogen of NFA. In addition to the above salts and cocrystals, supramolecular gels of NFA-PIP and NFA-BZA salts are reported, which were obtained from nitrobenzene, methyl salicylate, menthol, and mesitylene solvents. These gels were studied by rheology. Solubility and dissolution rate of the novel solid forms (NFA CPR, NFA PIP, NFA BSA, and NFA TYA) in 20% EtOH water showed the best behavior for NFA-TYA salt with improvement of 42-and 54-times in solubility and dissolution rate compared to the reference drug. The remaining solids such as NFA-PIP, NFA-BSA salts, and NFA-CPR cocrystal exhibited improvement of 39-, 18-, 1.4-times in solubility and 7.8-, 10-, 2-times for dissolution rate.

Crystalline acylhydrazone photoswitches with multiple mechanical responses - Gupta, Poonam; Panda, Tamas; Allu, Suryanarayana; Borah, Silpisikha; Baishya, Anamika; Gunnam, Anilkumar; Nangia, Ashwini; Naumov, Pance; Nath, Naba K. (Crystal Growth & Design, 2019)
The advancement of our understanding of stimuli responsive molecular crystals has led to the realization that they hold great yet unexplored potential as adaptive materials. Although molecular crystals that exhibit a single mechanical response to a single input stimulus are now abundant, crystals that are capable of response to multiple stimuli are rather scarce. Here we report two photoswitchable acylhydrazone derivatives, Ac-1 and Ac-2, which respond to light as well as to mechanical force. Upon application of localized mechanical stress, the anhydrous (Ac-1a) and monohydrate (Ac-1h) crystals of Ac-1 undergo plastic shearing deformation and bending, whereas monohydrate crystals of Ac-2 undergo elastic deformation. When they are exposed to UV light, crystals of Ac-1h and Ac-2 undergo photoinduced bending; on the other hand, crystals of Ac-1a and thicker crystals of Ac-2 exhibit photosalient effect (light-induced leaping). It is demonstrated that the synergistic action of multiple stimuli (UV light and force) elicits enhanced mechanical response, and this strategy could be employed in the future to increase the efficacy of single crystal actuators.